Caracterização de objeto simulador antropomórfico de tórax para medidas de dose em feixes de radiologia - Henriques, Laís Maria da Silva (2012)
The use of X-rays at procedures for purposes of medical diagnosis has increased over time. In these practices, it is necessary to weigh the patient s risks and benefits. To carry out periodic patient dose testing, phantoms, objects that simulate the interaction of ionizing radiation with the patient's body, are often used. The objective of this study was to characterize an anthropomorphic thorax phantom for dosimetric measurements at conventional radiology beams. This phantom was developed by a previous research project at the Federal University of Sergipe for image quality control tests. As the phantom consists of tissue equivalent material, it is possible to characterize it for dosimetric studies. For comparison, a geometric chest phantom, consisting of PMMA (polymethylmethacrylate) with dimensions of 30 cm x 30 cm x 15 cm, was used. With the use of ionization chambers, we performed measurements of incident air kerma (KIN) and entrance surface kerma (KES), which were compared with values estimated by calculation and diagnostic reference levels (NRDs). With these data, backscatter factors (BSF) of the two phantoms were calculated and compared with values estimated by Caldose software, based on Monte Carlo simulation. The variation of the BSF with the constituent material and technical parameters (kVp, mAs) and geometric (DFS) was studied. Doses to organs and effective doses for the anthropomorphic phantom were also estimated from the conversion coefficients (CCs) equivalent dose (H) and effective (E), through the Code Visual Monte Carlo (VMC). For combinations of technical parameters evaluated in this study, the ESD values obtained experimentally showed a good similarity to the two phantoms with maximum difference of 7%. There were no ESD values above the reference levels for diagnostic study. The results showed good agreement with the results published in the literature. It follows then, that the anthropomorphic thorax phantom proposed is a good tool to use in dosimetry.